A biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent and its preparation method and application
By grafting citric acid and chitosan on Mg/Al-LDHs, an efficient adsorbent was prepared, which solved the problem of easy agglomeration of existing adsorbent materials in water, significantly improved the adsorption capacity of metal ions, and Reduced production costs.
Patent Information
- Application Number
- CN202310408432.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-17
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-04-17
AI Technical Summary
Existing adsorbent materials are prone to agglomeration in water, resulting in poor adsorption effect on metal ions, high cost and difficult to regenerate, making it difficult to effectively reduce the concentration of metal ions in industrial wastewater.
Using biomass materials to graft the citric acid intercalation Mg/Al-LDHs adsorbent, modify Mg/Al-LDHs by citric acid, and graft chitosan on it, using N,N-methylenebisacrylamide As a linking agent, the adsorption ability of the adsorbent is enhanced.
It significantly improves the adsorption capacity of the adsorbent on metal ions, improves the adsorption amount of copper ions, enhances the dispersion and regenerative properties in water, and reduces production costs.
Smart Images

Figure BDA0004182397860000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorption materials, and in particular to a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent and a preparation method and application thereof. Background Art
[0002] With the progress of industrialization and urbanization, water, the source of life, has been increasingly polluted. Pollutants entering natural water bodies exceed the self-purification capacity of water bodies, causing pollution that will lead to water quality deterioration. Water pollution in my country is mainly caused by inorganic pollutants such as metal ions and organic pollutants. For example, printing and dyeing, smelting, electroplating, hardware, petrochemical and chemical industries all discharge large amounts of Cu-containing 2+ The toxicity of free copper ions is much greater than that of complex copper, which is not only very toxic to aquatic organisms, but also causes very serious damage to the natural environment. How to reduce the concentration of metal ions in waste liquid, improve water quality, thereby improving the efficiency of water recycling and reducing pollution to environmental water bodies is one of the most important directions and purposes of adsorbent research for many researchers. Among the existing methods, adsorption is the most widely used method. For a long time, many scientific researchers at home and abroad have been committed to the research and development and application of adsorbents. The high cost and difficulty in regeneration have limited the widespread use of existing adsorption materials, and also promoted people's scientific research on new adsorption materials with high economic benefits.
[0003] In the prior art, the hydrophilicity of organic acid-modified LDHs is lower than that of matrix LDHs, and it cannot effectively solve the problem of LDHs being easily agglomerated in water, thereby limiting its adsorption effect on metal ions in wastewater. Chitosan is low in price and has high adsorption efficiency. It is one of the most important biomass adsorption materials. It has a strong coordination ability for metal ions. This adsorption performance comes from the lone pair centers on the -NH2 and -OH on the chitosan molecular chain, which are relatively easy to form stable chelates with the empty orbitals of metal ions in the solution through coordination bonds. In order to effectively solve the more serious pollution problems in my country and achieve the sustainable development of biomatrix materials and the country, the use of chitosan and its application in other fields are of great significance to the green economy.
[0004] Chitosan is a recyclable renewable resource. Until recent decades, with the increasing prominence of environmental resource issues, people have gradually deepened their understanding of chitosan, and how to utilize it has received more and more attention.
[0005] In view of the above problems, it is of great significance to develop a new adsorption material with high adsorption performance using chitosan. Summary of the invention
[0006] In view of the above shortcomings of the prior art, the present invention provides a preparation method and application of a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent, which adopts the following technical scheme:
[0007] A biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent is disclosed. The adsorbent is firstly prepared by intercalating Mg / Al-LDHs with citric acid to obtain citric acid intercalated Mg / Al-LDHs; then chitosan is added to the citric acid intercalated Mg / Al-LDHs and N,N-methylenebisacrylamide is used as a linker to graft the citric acid intercalated Mg / Al-LDHs with chitosan, thereby preparing the biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent.
[0008] The present invention provides a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent. The preferred preparation method comprises the following steps:
[0009] S1. Citrate was dissolved in ethylene glycol, HNO3 was added, the pH value of the mixed solution was adjusted to acidic, magnesium aluminum layered double hydroxide (Mg / Al-LDHs) was added to the mixed solution, and then refluxed, cooled, filtered, washed and dried to obtain citric acid intercalated Mg / Al-LDHs;
[0010] S2. Adding acetic acid solution to chitosan, after ultrasonic oscillation, recorded as solution A; adding acetic acid solution to the citric acid intercalated Mg / Al-LDHs in step S1, after ultrasonic oscillation, recorded as solution B;
[0011] S3. Under the protection of inert gas, solution A and solution B are mixed and stirred evenly, and then N,N-methylenebisacrylamide is added. After stirring evenly again, NaOH is added to adjust the pH value to alkaline. After continuing to stir evenly, the mixture is filtered out, washed, dried, ground and sieved to obtain the biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent.
[0012] Furthermore, in step S1, the mass ratio of citrate to magnesium aluminum layered double hydroxide (Mg / Al-LDHs) is 9:(20-36).
[0013] Furthermore, in step S2, the mass ratio of chitosan to acetic acid solution is 1:(60-80), and the mass ratio of citric acid intercalated Mg / Al-LDHs to acetic acid solution is 1:(40-60).
[0014] Furthermore, the inert gas in step S3 is nitrogen or argon.
[0015] Furthermore, the citrate is one of sodium citrate, potassium citrate or calcium citrate.
[0016] Furthermore, in step S3, the mass ratio of the solution A to the solution B and the N,N-methylenebisacrylamide is (13-42):(47-65):(11-22).
[0017] Preferably, in step S3, the solution A is mixed with the solution B and N,N-methylenebisacrylamide in a mass ratio of 20:62:18.
[0018] Furthermore, the biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent obtained in step S3 adsorbs copper ions greater than 45 mg / g.
[0019] The invention also discloses an application of a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent, and the adsorbent can be applied to the treatment of heavy metal ions and polluted wastewater.
[0020] Compared with the prior art, the present invention is beneficial in that:
[0021] (1) The present invention combines chitosan with citric acid intercalated Mg / Al-LDHs, which not only retains the ability of citric acid intercalated Mg / Al-LDHs to adsorb copper ions, but also increases the binding sites of copper ions such as amino and hydroxyl groups in carboxymethyl chitosan for the prepared adsorbent. Under the combined action of the two, the adsorption capacity of the prepared adsorbent for metal ions is significantly improved.
[0022] (2) After citric acid is intercalated into LDHs, it cannot effectively inhibit the aggregation of LDHs. In the present invention, N,N-methylenebisacrylamide is selected as a linker to compound chitosan and citric acid intercalated Mg / Al-LDHs. As a dialdehyde linker, the polarized structure of the carbonyl group of N,N-methylenebisacrylamide makes it easy to undergo nucleophilic reaction with polar groups and bind tightly, so that the chitosan grafted citric acid intercalated Mg / Al-LDHs adsorbent of the present invention has a large rigid structure. Therefore, the chitosan grafted citric acid intercalated Mg / Al-LDHs has better dispersibility in water than the matrix LDHs. Through the grafting of N,N-methylenebisacrylamide, more adsorption groups in chitosan and citric acid intercalated Mg / Al-LDHs can be exposed, increasing the possibility of contact with metal ions. In addition, the amino group on the linker can also combine with copper ions in the wastewater. Combined with the characteristics of chitosan and citric acid intercalated Mg / Al-LDHs, the adsorption capacity of the prepared adsorbent for metal ions is further enhanced.
[0023] (3) Adsorbent materials prepared with chitosan as raw material can not only produce highly efficient adsorbents to solve the problem of heavy metal ion adsorption in industrial wastewater and expand the application field of chitosan, but also reduce the cost of wastewater adsorbents and solve the pollution treatment problem of papermaking waste pulp, ultimately achieving sustainable development, which is of great significance to the effective utilization of biomass-based materials and the significant improvement of the ecological environment in my country. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative labor are within the scope of protection of the present invention. Any equivalent transformation or substitution made by those skilled in the art based on the following implementation methods is within the scope of protection of the present invention.
[0025] The preferred preparation method of the biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent provided by the present invention comprises the following steps:
[0026] S1. Citrate was dissolved in ethylene glycol, HNO3 was added, and the pH value of the mixed solution was adjusted to 3-6. Then, magnesium aluminum-based layered double hydroxide (Mg / Al-LDHs) was added to a three-necked flask in a mass ratio of citrate to magnesium aluminum-based layered double hydroxide (Mg / Al-LDHs) of 9:(20-36). Finally, the mixture was refluxed at 115-125°C for 4-6h, cooled to room temperature, filtered, washed with deionized water for 2-3 times, and dried at 75-85°C for 11-13h to obtain citric acid intercalated Mg / Al-LDHs.
[0027] S2. Dissolve chitosan in acetic acid solution in a flask so that the mass ratio of chitosan to acetic acid solution is 1: (60-80), and then disperse and dissolve it by ultrasonic oscillation, which is recorded as solution A; dissolve the citric acid intercalated Mg / Al-LDHs and acetic acid solution in step S1 in a mass ratio of 1: (40-60), and then disperse and dissolve it by ultrasonic oscillation, and record it as solution B;
[0028] S3. Under the protection of inert gas, the prepared solution A and solution B are mixed in a mass ratio of (13-42): (47-65), stirred at a constant speed at room temperature for 1-1.5 hours, and then N,N-methylenebisacrylamide is added to make the mass ratio of solution A to N,N-methylenebisacrylamide be (13-42): (11:22), and stirring is continued at 40-45°C for 1-2 hours, and then the pH is adjusted to about 8-10 with 1 mol / L NaOH, followed by stirring at 65-75°C for 1-2 hours, and finally filtered, washed with anhydrous ethanol and deionized water for 2-3 times respectively, dried at 75-85°C for 11-13 hours, ground and sieved through a 200-mesh sieve to obtain a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent.
[0029] In the following examples and comparative examples, sodium citrate, ethylene glycol, dilute nitric acid, layered double hydroxide, acetic acid, N,N-methylenebisacrylamide, NaOH, and anhydrous ethanol were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and all raw materials are common raw materials on the market.
[0030] Example 1
[0031] A method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent comprises the following steps:
[0032] S1. Sodium citrate was dissolved in ethylene glycol in a three-necked flask, and an appropriate amount of 0.1 mol / L HNO3 was added to adjust the pH value of the mixed solution to 5. Then, magnesium aluminum-based layered double hydroxide (Mg / Al-LDHs) was added to the three-necked flask in a mass ratio of 9:20 between sodium citrate and magnesium aluminum-based layered double hydroxide (Mg / Al-LDHs). Finally, the mixture was refluxed at 120°C for 5h, cooled to room temperature, filtered, washed three times with deionized water, and dried at 80°C for 12h to obtain citric acid intercalated Mg / Al-LDHs.
[0033] S2. Dissolve chitosan in 2% acetic acid solution in a flask so that the mass ratio of chitosan to 2% acetic acid solution is 1:60, and then disperse and dissolve it by ultrasonic oscillation, which is recorded as solution A; dissolve the citric acid intercalated Mg / Al-LDHs and 2% acetic acid solution in step S1 in a mass ratio of 1:40, and then disperse and dissolve it by ultrasonic oscillation, and record it as solution B;
[0034] S3. Under nitrogen protection, the prepared solution A and solution B were mixed in a mass ratio of 13:65, stirred at room temperature for 1 hour, and then N,N-methylenebisacrylamide was added to make the mass ratio of solution A to N,N-methylenebisacrylamide 13:22. Stirring was continued at 40°C for 1.5 hours, and then the pH was adjusted to about 9 with 1 mol / L NaOH, followed by stirring at 70°C for 1 hour, and finally filtered, washed three times with anhydrous ethanol and deionized water respectively, dried at 80°C for 12 hours, ground and sieved through a 200-mesh sieve to obtain a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent.
[0035] Example 2
[0036] A method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent. This embodiment is basically the same as embodiment 1, except that in step S3, the mass ratio of solution A to solution B and N,N-methylenebisacrylamide is 20:62:18.
[0037] Example 3
[0038] A method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent, this embodiment is basically the same as embodiment 1, the difference is that in step S3, the mass ratio of solution A to solution B and N,N-methylenebisacrylamide is 31:54:15.
[0039] Example 4
[0040] A method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent, this embodiment is basically the same as embodiment 1, the difference is that in step S3, the mass ratio of solution A to solution B and N,N-methylenebisacrylamide is 42:47:11.
[0041] Example 5
[0042] A method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent. This embodiment is basically the same as embodiment 1, except that in step S1, the mass ratio of sodium citrate to magnesium aluminum layered double hydroxide (Mg / Al-LDHs) is 9:35; in step S2, the mass ratio of chitosan to 2% acetic acid solution is 1:78, and the mass ratio of citric acid intercalated Mg / Al-LDHs to 2% acetic acid solution is 1:60.
[0043] Comparative Example 1
[0044] A method for preparing a chitosan adsorbent. The chitosan adsorbent provided in this comparative example is prepared according to the following method:
[0045] The chitosan material was directly dried at 80° C. for 12 h, ground and passed through a 200-mesh sieve to obtain a chitosan powder adsorbent.
[0046] That is, compared with Example 1, chitosan is directly used to adsorb copper ions in this comparative example.
[0047] Comparative Example 2
[0048] A method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent. This comparative example is basically the same as Example 1, except that in step S3, no N,N-methylenebisacrylamide linker is added, and the chitosan solution is directly blended with the citric acid intercalated Mg / Al-LDHs solution.
[0049] Comparative Example 3
[0050] A method for preparing a citric acid intercalated Mg / Al-LDHs adsorbent. The citric acid intercalated Mg / Al-LDHs adsorbent provided in this comparative example is prepared according to the following method:
[0051] S1. Sodium citrate was dissolved in ethylene glycol in a three-necked flask, and an appropriate amount of 0.1 mol / L HNO3 was added to adjust the pH value of the mixed solution to 5. Layered double hydroxide was added to the three-necked flask in a mass ratio of sodium citrate to magnesium aluminum layered double hydroxide (Mg / Al-LDHs) of 9:20. The mixture was refluxed at 120°C for 5h, cooled to room temperature, filtered, and washed three times with deionized water, and dried at 80°C for 12h to obtain citric acid intercalated Mg / Al-LDHs;
[0052] S2. The citric acid intercalated Mg / Al-LDHs and 2% acetic acid solution in step S1 are dissolved in a mass ratio of 1:40, and then N,N-methylenebisacrylamide is added to make the mass ratio of citric acid intercalated Mg / Al-LDHs to N,N-methylenebisacrylamide be 65:22, and stirring is continued at 40°C for 1.5h, and then the pH is adjusted to about 9 with 1mol / L NaOH, and then stirred at 70°C for 1h, and finally filtered, washed three times with anhydrous ethanol and deionized water respectively, dried at 80°C for 12h, ground and sieved through a 200-mesh sieve to obtain a citric acid intercalated Mg / Al-LDHs adsorbent.
[0053] That is, compared with Example 1, chitosan was not used to graft the citric acid intercalated Mg / Al-LDHs in this comparative example.
[0054] Comparative Example 4
[0055] A method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent comprises the following steps:
[0056] S1. Dissolve chitosan in 2% acetic acid solution in a flask so that the mass ratio of chitosan to 2% acetic acid solution is 1:60, and then disperse and dissolve it by ultrasonic oscillation, which is recorded as solution A; dissolve Mg / Al-LDHs and 2% acetic acid solution in a mass ratio of 1:40, and then disperse and dissolve it by ultrasonic oscillation, which is recorded as solution B;
[0057] S2. Under nitrogen protection, the prepared solution A and solution B were mixed in a mass ratio of 13:65, stirred at room temperature at a constant speed for 1 hour, and then a certain amount of N,N-methylenebisacrylamide was added to make the mass ratio of solution A to N,N-methylenebisacrylamide 13:22, and stirred at 40°C for 1.5 hours, and then 1 mol / L NaOH was used to adjust the pH to about 9, and then stirred at 70°C for 1 hour, and finally filtered, washed with anhydrous ethanol and deionized water three times respectively, and dried at 80°C for 12 hours to obtain chitosan grafted Mg / Al-LDHs;
[0058] S3. Dissolve sodium citrate in ethylene glycol in a three-necked flask, add an appropriate amount of 0.1 mol / L HNO3 to adjust the pH value of the mixed solution to 5, and then add chitosan grafted Mg / Al-LDHs to the three-necked flask in a mass ratio of sodium citrate to chitosan grafted Mg / Al-LDHs of 9:20. Finally, reflux the mixture at 120°C for 5 hours, cool to room temperature, filter, and wash three times with deionized water, dry at 80°C for 12 hours, grind and pass through a 200-mesh sieve to obtain a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent.
[0059] That is, compared with Example 1, in this comparative example, Mg / Al-LDHs is first grafted with chitosan and then modified by intercalation with citric acid.
[0060] Comparative Example 5
[0061] A method for preparing a chitosan-grafted Mg / Al-LDHs adsorbent comprises the following steps:
[0062] S1. Dissolve chitosan in 2% acetic acid solution in a flask so that the mass ratio of chitosan to 2% acetic acid solution is 1:60, and then disperse and dissolve it by ultrasonic oscillation, which is recorded as solution A; dissolve Mg / Al-LDHs and 2% acetic acid solution in a mass ratio of 1:40, and then disperse and dissolve it by ultrasonic oscillation, which is recorded as solution B;
[0063] S2. Under nitrogen protection, the prepared solution A and solution B were mixed in a mass ratio of 13:65, stirred at room temperature for 1 hour, and then N,N-methylenebisacrylamide was added to make the mass ratio of solution A to N,N-methylenebisacrylamide 13:22. Stirring was continued at 40°C for 1.5 hours, and then the pH was adjusted to about 9 with 1 mol / L NaOH, followed by stirring at 70°C for 1 hour, and finally filtered, washed three times with anhydrous ethanol and deionized water respectively, dried at 80°C for 12 hours, ground and passed through a 200-mesh sieve to obtain a chitosan-grafted Mg / Al-LDHs adsorbent.
[0064] That is, compared with Example 1, in this comparative example, chitosan is directly grafted onto Mg / Al-LDHs without using citric acid intercalation modification.
[0065] Application Example 1
[0066] Analytical reagent grade Cu(NO3)·3H2O was added to deionized water to prepare 1L of Cu with an initial concentration of 200mg / L. 2+ solution, and then weigh 1g of adsorbent and add Cu 2+ The solution was stirred at a constant speed for 3 h at 25 °C, and the adsorbed Cu 2+ concentration.
[0067] The present invention is further described in detail below in conjunction with the examples and comparative examples: The equilibrium adsorption amount mentioned in the test is the result of the adsorbent reaching equilibrium by oscillating adsorption of a certain concentration of metal cation solution. The concentration of metal ions before and after adsorption is determined by atomic absorption spectrophotometry, and the adsorption amount is calculated by the following formula:
[0068]
[0069] In the formula, q e is the equilibrium adsorption amount, recorded in mg / g, Co is the initial concentration of metal ions in the waste liquid before adsorption, recorded in mg / L, Ce is the equilibrium concentration of metal ions in the remaining waste liquid after adsorption, recorded in mg / L, m is the mass of the adsorbent, recorded in g, V is the volume of the metal waste liquid, recorded in L, and the test results are listed in Table 1.
[0070] Table 1 Adsorption of Cu by adsorbents prepared in various embodiments and comparative examples 2+ Test results
[0071] Adsorbent sample Adsorption Example 1 55.4mg / g Example 2 64.6mg / g Example 3 59.3mg / g Example 4 47.7mg / g Example 5 54.1mg / g Comparative Example 1 33.4mg / g Comparative Example 2 39.4mg / g Comparative Example 3 34.7mg / g Comparative Example 4 37.5mg / g Comparative Example 5 35.3mg / g
[0072] As can be seen from Table 1, the adsorbent prepared in Example 2 has the highest copper adsorption content, and the adsorbent prepared in Comparative Example 1 has the least copper adsorption content. Compared with Example 1, Comparative Example 1 directly uses chitosan for adsorption, and its adsorption amount is less than that of the adsorbent prepared in the present invention. The reason may be that natural chitosan only has its own adsorption groups, and its adsorption effect on metal ions is relatively limited; compared with Example 1, Comparative Example 2 does not use the linker N, N-methylenebisacrylamide, so that there is no grafting reaction between chitosan and citric acid Mg / Al-LDHs, which cannot improve the dispersion effect of Mg / Al-LDHs, resulting in poor adsorption of the adsorbent in Comparative Example 2; compared with Example 1, Comparative Example 3 does not use chitosan to graft citric acid intercalated Mg / Al-LDHs, and the adsorption amount of the adsorbent obtained is less than that of the adsorbent prepared in the present invention. This is because the hydroxyl and amino groups contained in chitosan can increase the adsorption group of citric acid intercalated Mg / Al-LDHs. group, increasing its binding sites with metal ions and improving its ability to adsorb copper ions; compared with Example 1, the adsorption amount of the adsorbent prepared by first grafting Mg / Al-LDHs with chitosan and then modifying it with citric acid intercalation in Comparative Example 4 is worse than that of the adsorbent prepared in the present invention, and the reason may be that the solubility of LDHs in the solution will be affected after grafting LDHs with chitosan, making it difficult to implement intercalation with citric acid; compared with Example 1, the adsorption amount of the adsorbent obtained by not modifying LDHs with citric acid intercalation in Comparative Example 5 is worse than that of the adsorbent prepared in the present invention, because Mg / Al-LDHs not modified with citric acid intercalation does not have the function of citric acid chelating copper ions, and can only rely on free hydroxyl groups for adsorption. Even if it is compatible with chitosan, the adsorption effect of the obtained adsorbent on metal ions is still relatively limited.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. For any person skilled in the art, the present invention may have various changes and modifications. Any simple equivalent changes and modifications made according to the scope of protection of the present invention and the contents of the specification should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent, characterized in that: First, Mg / Al-LDHs were intercalated and modified with citric acid to obtain citric acid intercalated Mg / Al-LDHs; then, chitosan was added to the citric acid intercalated Mg / Al-LDHs, and N,N-methylenebisacrylamide was used as a linker to graft the citric acid intercalated Mg / Al-LDHs with chitosan to prepare a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent for adsorbing heavy metal ions.
2. The method for preparing the biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent according to claim 1, characterized in that: The following steps are involved: S1. Dissolve citrate in ethylene glycol, add HNO3, adjust the pH value of the mixed solution to acidic, add magnesium aluminum layered double hydroxide (Mg / Al-LDHs) to the mixed solution, reflux, cool, filter, wash and dry to obtain citric acid intercalated Mg / Al-LDHs; S2. Adding acetic acid solution to chitosan, after ultrasonic oscillation, recorded as solution A; adding acetic acid solution to the citric acid intercalated Mg / Al-LDHs in step S1, after ultrasonic oscillation, recorded as solution B; S3. Under the protection of inert gas, the solution A and the solution B are mixed and stirred evenly, and then N,N-methylenebisacrylamide is added. After stirring evenly again, NaOH is added to adjust the pH value to alkaline. After continuing to stir evenly, the mixture is filtered out by suction, washed, dried, ground and sieved to obtain the biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent.
3. The method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent according to claim 2, characterized in that: The mass ratio of the citrate to the magnesium aluminum layered double hydroxide (Mg / Al-LDHs) in step S1 is 9:(20-36).
4. The method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent according to claim 2, characterized in that: In step S2, the mass ratio of the chitosan to the acetic acid solution is 1:(60-80), and the mass ratio of the citric acid intercalated Mg / Al-LDHs to the acetic acid solution is 1:(40-60).
5. The method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent according to claim 2, characterized in that: The citrate is one of sodium citrate, potassium citrate or calcium citrate.
6. The method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent according to claim 2, characterized in that: The inert gas in step S3 is nitrogen or argon.
7. The method for preparing a biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent according to claim 2, characterized in that: In step S3, the mass ratio of the solution A to the solution B and the N,N-methylenebisacrylamide is (13-42): (47-65): (11-22).
8. A biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent, characterized in that: The method is prepared by any one of claims 1 to 7.
9. An application of the biomass material grafted citric acid intercalated Mg / Al-LDHs adsorbent according to claim 8, characterized in that: Used in the treatment of heavy metal ions and polluted wastewater.
Citation Information
Patent Citations
Preparation method of chitosan-hydrotalcite nanocomposite material
CN108993430A